Preparation and Characterisation of Bismuth Zinc Tantalate Pyrochlore Materials - Khaw, Chwin Chieh (2007)
Pyrochlore materials in Bi2O3-ZnO-Ta2O5 ternary system were synthesized by solid-state reaction at 1050oC for 48 hours. The X-ray diffraction (XRD) pattern of the material of composition Bi3Zn2Ta3O14 could be fully indexed on a cubic cell with a = 10.5437(9) Å. A study on the phase formation mechanism indicated that Bi2O3 played an important role only in the initial stage of the formation of the pyrochlore phase. The subsolidus phase diagram of Bi2O3-ZnO-Ta2O5 in the region of the cubic pyrochlore has been determined at 1050oC. This phase forms a solid solution area that includes the ideal composition P, Bi3Zn2Ta3O14. Density measurement was used to identify the possible mechanism of solid solution formation. The solid solution area in the phase diagram can be described by the combination of two mechanisms: Bi3Zn2-xTa3O14-x and Bi3+yZn2Ta3-yO14-y, to yield the formula Bi3+yZn2-xTa3-yO14-x-y, -0.20 ≤ y ≤ 0.16 and 0.00 ≤ x ≤ 0.40. XRD in combination with neutron diffraction data were used for Rietveld Refinement for the elucidation of the crystal structure of selected materials. The results show that there is a degree of insensitivity of the refinement to certain changes in the cation content and the oxygen stoichiometry is refined to a value similar to the expected values.